Increased free water in the nucleus basalis of Meynert is associated with worse olfaction in idiopathic Parkinson’s disease - Wei, Kai; Wang, Shuyue; Zhou, Cheng; Huang, Peiyu; Wang, Chao (Frontiers in Aging Neuroscience, 2025)
BackgroundThe association of cholinergic degeneration and olfactory function in Parkinson’s disease (PD) is unclear. Using free water imaging, this study aims to investigate the association between the nucleus basalis of Meynert (NBM) degeneration and olfactory function in patients with PD.MethodsA total of 281 idiopathic patients with PD and 98 healthy controls with diffusion tensor MRI data were included from the Parkinson’s Progression Markers Initiative (PPMI) dataset. Olfactory function was assessed by the University of Pennsylvania Smell Identification Test (UPSIT). Free water and volume of the NBM were measured and compared between the two groups. Furthermore, correlation analyses were performed to determine the association between the free water and volume of the NBM and clinical measures in patients with PD. Then, the discriminative power of the free water was evaluated between PD patients with hyposmia and without hyposmia by receiver operating characteristic curve (ROC) analysis.ResultsNucleus basalis of Meynert free water showed a trend toward increase in PD patients compared with healthy controls (p = 0.064), while NBM volume showed no significant difference between patients with PD and healthy controls (p = 0.393). Pearson correlation analyses revealed significant correlations between age and free water (r = 0.252, p < 0.001) and volume (r = −0.48, p < 0.001) of NBM in patients with PD. Pearson correlation analyses showed NBM free water was negatively correlated with UPSIT scores (p < 0.001), while NBM volume was positively correlated with UPSIT scores (p = 0.002) in patients with PD. Partial correlation analyses were further performed adjusting for age, the results showed NBM free water remained significantly negatively correlated with UPSIT score (p = 0.013), while NBM volume was not significantly correlated with UPSIT score in patients with PD (p = 0.461). In addition, ROC analysis showed that NBM free water identified PD patients with hyposmia at high sensitivity (81.6%).ConclusionOur study demonstrated that the free water of the NBM was associated with worse olfaction in idiopathic patients with PD. Our study suggests that free water in the NBM has the potential to provide early biomarkers of olfaction dysfunction in idiopathic patients with PD.